TYPES OF DIRECTIVE SPEECH ACTS USED BY FUTSAL COACH IN VAMOS ACADEMY PADANG - Dermawan, Adit; AS, Rina Marnita; Revita, Ike (TELL - US JOURNAL, 2020)
This study aims to describe the types of directive speech acts used by futsal coach in Vamos Academy Padang. This research uses a descriptive qualitative approach. The researcher uses speech act theory proposed by Searle (1979) and speech act theory proposed by Kreidler (1998) in analyzing data. The data in this study are the utterances of coach toward the students which are contain the intention of directive. The data were collected using observation methods and recording techniques. The results showed that the coach used three types of directive speech acts in communicating with students when coaching in Vamos Academy Padang. The three types of directive speech acts are commands, requests and suggestions. From the three types of directive speech acts, command is the type of directive that is most often used by coach toward the students in Vamos Academy Padang with 59%. Furthermore, it is followed by request with 26% and suggestion with 15%. The use of dominant command by the coach toward students in Vamos Academy Padang is influenced by the participant context in the utterance where the coach is the coaching leader in the field who has the authority and responsibility for the success of the material given to students in the exercise.